Seroprevalence and the Associated Risk Factors of Toxoplasma Gondii Infection among Pregnant Women in The Middle Belt of Ghana - Adu Mensah, Derrick; Debrah, Linda Batsa; Bonney, Richard Abeiku; Bhavana, Singh; Bortie, Patience; Safo, Rebecca; Aryee, Clement Evans; Debrah, Alexander Yaw (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Exposure to Toxoplasma gondii infection is prevalent in up to 90% of the world’s human population. Severe infections can be fatal and deforming in neonates, with cats serving as reservoirs for T. gondii infections. The objective of this study was to determine the seroprevalence of Toxoplasma gondii infection and its associated risk factors among pregnant women in the middle belt of Ghana. Subjects and Method: This was a cross-sectional study involving 266 pregnant women from two health facilities in the middle belt of Ghana. A structured questionnaire was administered to the participants to gather information on exposure to the associated infection risk factors and demography. In addition, 3ml of venous blood was collected from each participant for anti-Toxoplasma gondii IgG/IgM antibody analyses. Results: A total of 64.3% of the study population had been exposed, whiles 26.3% were actively infected, being seropositive respectively to anti-Toxoplasma gondii IgG/IgM antibodies. In both districts, significant differences were recorded between anti-T. gondii IgG and IgM seroprevalences (95% CI= 0.00 to 0.02; p<0.001). There was no statistical difference observed between the participants’ mean antibody concentration levels and age (95% CI= 0.74 to 0.85; p=0.637) as well as the stage of pregnancy (95% CI= 0.38 to 0.43; p= 0.127). Also, no strong association (OR<0.6) was found between seropositivity and the suspected risk factors assessed in the study. Conclusion: The study showed that the seroprevalence of T. gondii infection among pregnant women visiting the two health facilities in the two regions was higher compared to the 30%-65% reported as the global population infection status. This study provides baseline data for future studies in other Districts and Regions in the country to ascertain the overall seroprevalence in Ghana and also push for a national programme/ policy for routine clinical screening of toxoplasmosis in pregnant women. Keywords: seroprevalence, Toxoplasma gondii, pregnant women, anti-T. gondii IgG/IgM antibodies. Correspondence: Derrick Adu Mensah, Department of Clinical Microbiology, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana/Kumasi Center for Collaborative Research in Tropical Medicine, KCCR, Kumasi, Ghana. Mobile: +2332-6168-6052. Email: derrickadumensah@yahoo.com.